Determination of L-Type Calcium Current in the Primary Hypertrophied Left Ventricular Cardiomyocytes of Hypertrophy Heart Rats/HHR - Vennetia R. Danes (MEDIA MEDIKA INDONESIANA, 2009)
Background: The molecular mechanisms responsible for electromechanical derangements found in primary left ventricular (LV) hypertrophy have not been clearly elucidated. Of particular interest is the voltage gated L-type Ca current (ICa L) which plays crucial role in the EC-coupling. This study aimed to investigate cardiomyocyte ICa(L) in newly developed line of rats namely HHR (hypertrophy heart rat) and NHR (normal heart rat).Methods: A pure experimental study has been conducted using male HHR (n=7 rats) and NHR (n=9 rats), aged 19-25 week. Cardiomyocytes were isolated enzymatically. By using whole cell patch clamp techniques, ICa were measured and normalized (pA/pF) for cell size determined by capacitance (Cm). In Na-free superfusate, the ICa(L) of HHR (n=18 cells) and NHR (n=12 cells) obtained at holding potential (HP) -50 mV were analyzed using Student’s t-test and one-way ANOVA (repeated measures). p<0.05values were considered significance.Results: Myocyte mean Cm of HHR slightly increased but not significantly greater than that of NHR (364.3±22.33 pF vs 300.2±27.78 pF, p=0.08). In HHR, peak Ca current density was significantly increase, i.e, at HP -50 mV, the ICa(L) evoked at test potential (TP) -10 mV were -7.74±0.86 (HHR) vs -4.68±1.09 (NHR) pA/pF, p<0.02.Conclusions: Peak Ca current density of HHR increases approximately 1.6 times that of the NHR (-7.74±0.86 vs -4.68±1.09 pA/pF). This increase is attributed primarily to L-type Ca current, best known to peak at around TP -10 mV. The dramatic increase in sarcolemmal calcium influx in the HHR provides evidence of altered EC coupling processes in primary LV hypertrophy.Keywords: HHR rats, LV hypertrophy, cardiomyocyte, L-type calcium currentABSTRACT Penentuan arus kalsium tipe L pada kardiomiosit tikus yang mengalami hipertrofi primer ventrikel kiri (Hypertrophy Heart Rats/HHR)Latar belakang: Mekanisme molekuler yang bertanggung jawab pada munculnya kelainan elektro-mekanik pada hipertrofi primer ventrikel kiri masih belum jelas, khususnya arus kasium tipe L, ICa(L), yang berperan penting pada ‘EC-coupling’. Tujuan penelitian ini untuk mengukur dan menganalisis ICa(L) kardiomiosit dari tikus jenis baru bernama HHR (hypertrophy heart rat) dan NHR (normal heart rat).Metode: Eksperimen murni laboratorik dilakukan pada tikus jantan NHR (n=9) dan HHR (n=7) berusia 19-25 minggu. Kardiomiosit diisolasi menggunakan teknik enzimatika. Dengan teknik ‘whole cell patch clamp’; arus kalsium ICa(L) diukur dan dinormalisasi sesuai ukuran selnya (pA/pF), yang ditentukan melalui pengukuran kapasitans membran (Cm). Pada kondisi bebas Na, ICa(L) dari kedua kelompok sel HHR (n=18) dan NHR (n=12), yang didapat dari ‘holding potential’ (HP) -50mV dianalisis dengan Student’st-test dan one-way ANOVA (repeated measures). Nilai p<0,05 dianggap bermakna.Hasil: Rerata kapasitans membran (Cm) dari HHR dan NHR secara statistik tidak beda secara bermakna (364,3±22,33 pF vs 300,2±27,78 pF, p=0,08). Pada HP -50 mV, densitas arus kalsium ICa(L) yang dihasilkan dari ‘test potential’ (TP)-10 mV meningkat secara bermakna pada HHR dibanding NHR -7,74±0,86 vs -4,68±1,09 pA/pF (p<0,02).Simpulan: Terjadi peningkatan densitas arus kalsium pada HHR yaitu 1,6 kali NHR (-7,74±0,86 vs -4,68±1,09 pA/pF). Peningkatan ini seluruhnya disebabkan oleh ICa(L), karena tipe ini biasanya memuncak pada TP sekitar -10 mV. Peningkatan influx kalsium sarkolemma HHR yang sangat besar ini, merupakan bukti adanya perubahan proses ‘EC coupling’ pada ventrikel kiri yang mengalami hipertrofi primer.